ARQUIMUSICAR A TRAVÉS DE LA TRANSDISCIPLINARIDAD, ENTRE LO SUBLIME DE LA SONORIDAD Y LO METAFÓRICO DE LA ESPACIALIDAD - Barahona Israel, María de los Ángeles (2015)
The article aims to provide knowledge about the interplay of Architecture, Musical Arts, sound-space, Physics and acoustics; emphasizing the search for conceptual bridges, intersections or transdisciplinary parallelisms and removing boundaries between these fields of knowledge. Progress on the state of art of these areas are documented, presenting theoretical references on current spatial sound complexities of today’s experiential world. Specific experiences of this complexity are narrated through the course Arquimusicar, developed in a transdisciplinry way, at the School of Architecture at the University of Costa Rica. The course presents innovative methodologies in teaching-learning processes from exploratory, phenomenological and transdisciplinary prospects, achieving to research new “echoes”, atmospheres and specific meanings of sound-space issues in various construction areas and in today’s city ; erasing boundaries between arts and science. In that sense, academic experiences of Arquimusicar during the years 2013 and 2014, contribute with perceptions and multi-sensory methods based on cultural, spatial, environmental, psychological, landscape and acoustic aspects, developing a “transdisciplinary hybridization” of innovative and comprehensive teaching–learning process for the XXI Century, propicious for current scenarios of Higher Education.